A mechanism for repression of class II gene transcription through specific binding of NC2 to TBP-promoter complexes via heterodimeric histone fold domains. - Goppelt, A (1996)
Negative co-factor 2 (NC2) regulates transcription of the class II genes through binding to TFIID and inhibition of pre-initiation complex formation. We have isolated and cloned NC2, and investigated the molecular mechanism underlying repression of transcription. NC2 consists of two subunits, termed NC2alpha and NC2beta, the latter of which is identical to Dr1. The NC2 subunits dimerize and bind to TATA binding protein (TBP)-promoter complexes via histone fold domains of the H2A-H2B type. Repression of basal transcription requires the histone fold and carboxy-terminal domains of the NC2 subunits. Several mechanisms probably contribute to transcriptional repression. Binding of NC2 inhibits association of TFIIB with TBP-promoter complexes. NC2 binds directly to DNA, and binding of NC2 to TBP-promoter complexes affects the conformation of DNA, which could be one cause for the inhibition of TFIIB. In addition, multimerization of repressor-TBP complexes on DNA might inhibit the assembly of the pre-initiation complex. We suggest that binding of the repressor to TRP-promoter complexes establishes a mechanism that controls the rate of transcription by RNA polymerase II.